Nigella Sativa dalam Menurunkan Manifestasi Klinis COVID-19 melalui Efek Imunomodulator - Salwa Naura Kamila (Jurnal Ilmu Kesehatan dan Gizi, 2025)
COVID-19 is caused by the SARS-CoV-2 virus which infects the respiratory system and transmitted by droplets. This study aims to see the effect of administering Nigella sativa which has an immunomodulatory effect in reducing the clinical manifestations of COVID-19 disease by increasing the immune system. The method used is a literature review of five selected journals through a prism diagram flow from the PubMed, SpringerLink, and ScienceDirect electronic databases. Clinical manifestations of COVID-19 in patients decreased the length of patients’ hospital stay which become shorter in the intervention group compared to the control group. Nigella sativa has a positive response to increasing immunity. The immunomodulatory effect of NS is proven in increasing macrophage phagocytosis, immunoglobulin titer, lymphocyte ratio, and preventing T cell depletion and encouraging specific T cell proliferation.